Ethnobotany of India, Volume 3 : North-East India and the Andaman and Nicobar Islands - Pullaiah, T.; Krishnamurthy, K. V.; Bahadur, Bir. (Apple Academic Press, 2017)
"Ethnobotany of India: Volume 3: North-East India and Andaman and Nicobar Islands is the third of a five-volume set of Ethnobotany of India. Bringing together in one place the important information on the ethnobotany of the North-East India and Andaman and Nicobar Island region of India, this informative volume presents the details of the tribes of the region, their numbers, their habitat, their culture, and particularly their usage of plants for various purposes."--Provided by publisher.
Chapter Acknowledgements -- chapter Ethnobotany of India 5-volume Series -- chapter About the Editors -- chapter 1 Introduction -- chapter 2 Ethnic Diversity of North-East India -- chapter 3 Ethnoagriculture in North-East India: Pros, Cons, and Eco-Sustainable Model -- chapter 4 Ethnic Food Plants and Ethnic Food Preparation of North-East India -- chapter 5 Ethnomedicinal Plants of North-East India -- chapter 6 Ethnobotany of Other Useful Plants in North-East India: An Indo-Burma Hot Spot Region -- chapter 7 Ethnoveterinary Practices in Northeast India and Andamans -- chapter 8 Ethnobotany of Andaman and Nicobar Islands -- chapter 9 Documentation and Exchange of Ethnobotanical Knowledge -- chapter 10 Quantitative Ethnobotany: Its Importance in Bioprospecting and Conservation of Phytoresources -- chapter 11 Ethnobotany of Turmeric and Its Medicinal Importance -- chapter 12 Traditional Use of Herbal Plants for the Treatment of Diabetes in India -- chapter 13 Ethnobotany of Oral and Dental Problems in India.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE -- Life Sciences -- Botany; TECHNOLOGY & ENGINEERING -- Food Science; Ethnobotany -- India -- Andaman and Nicobar Islands